Evaluating the impact of Zanjan city’s economic drivers on the quality of life in peri-urban villages: a case study of Do Asb and Payin Kouh villages - Ali Shamaei; Kamran Jafarpour Ghalehteimouri (Frontiers of Urban and Rural Planning, 2024)
Abstract The interplay between urban centers and peri-urban villages plays a pivotal role in rural development, particularly in the economic dimension. Analyzing these relationships and their influence on the progress and prosperity of peri-urban villages, coupled with capacity building, empowerment, and the integration of urban-rural management, is essential to reduce disparities and promote spatial justice, aligning with the sustainable development of rural areas. This study aims to assess the effects of Zanjan city's economic drivers on the livability quality of Do Asb and Payin Kouh, two peri-urban villages situated in Zanjan city. Employing a descriptive-analytical and practical approach, the study's statistical population comprises the aforementioned villages in Zanjan city. A sample of 219 households was selected from among the sample population based on Cochran's formula. Data collection involved both library research and fieldwork, including the use of questionnaires. Descriptive and inferential statistics (multivariate regression) were employed for data analysis, along with descriptive statistics (averages) and geographic information systems to analyze land use changes. The research findings unveiled a robust correlation (0.87) between the quality of life in peri-urban villages and the economic drivers of Zanjan city. This indicates a significant and positive relationship between Zanjan city's economic drivers (independent variable) and the quality of life in peri-urban villages (dependent variable). Among the examined variables, communication flow for purchases, with a coefficient of 0.28, contributed most to the variance analysis of the quality of life in peri-urban villages. In contrast, the investment flow of urban residents in village economic activities and the flow of money exchange had relatively lower coefficients of 0.13 and 0.14, respectively. Thus, the research underscores the considerable impact of Zanjan's economic drivers on enhancing the quality of life in peri-urban villages and highlights the pivotal role of rural-urban links in fostering sustainable rural development.